TCV divertor upgrade for alternative magnetic configurations. (August 2017) - Reimerdes, H.; Alberti, S.; Blanchard, P.; Bruzzone, P.; Chavan, R.; Coda, S.; Duval, B.P.; Fasoli, A.; Labit, B.; Lipschultz, B.; Lunt, T.; Martin, Y.; et al.
Abstract: The Swiss Plasma Center (SPC) is planning a divertor upgrade for the TCV tokamak. The upgrade aims at extending the research of conventional and alternative divertor configurations to operational scenarios and divertor regimes of greater relevance for a fusion reactor. The main elements of the upgrade are the installation of an in-vessel structure to form a divertor chamber of variable closure and enhanced diagnostic capabilities, an increase of the pumping capability of the divertor chamber and the addition of new divertor poloidal field coils. The project follows a staged approach and is carried out in parallel with an upgrade of the TCV heating system. First calculations using the EMC3-Eirene code indicate that realistic baffles together with the planned heating upgrade will allow for a significantly higher compression of neutral particles in the divertor, which is a prerequisite to test the power dissipation potential of various divertor configurations. Highlights: Planned divertor upgrade seeks to enhance TCV's capabilities to study detachment in conventional and alternative configurations towards regimes of greater relevance for ITER and DEMO. First phase foresees the installation of gas baffles to form a divertor chamber of variable closure and enhancements of divertor diagnostics. Second phase may add a cryogenic pump for independent control of the neutral density in the divertor and the electron density of the plasma. Third phase may add new divertor coils to improve control and increase the range of divertor configurations.